THE IMPACT OF NEW FINANCIAL INSTRUMENT AND LEASE ACCOUNTING STANDARD ON FINANCIAL PERFORMANCE OF COMPANIES - Saiful Saiful; Nurna Aziza; Husaini Husaini; Nikmah Nikmah; Karina Dwi Fortuna (EKUITAS (Jurnal Ekonomi dan Keuangan), 2023)
The purpose of this study to examine the impact of new accounting standard of finansial instrument (PSAK 71) and lease (PSAK 73) on financial performance and liabilities of Indonesia listed companies. By applying the purposive sampling method, 140 companies for 2019 and 2020 were selected as the sample of this study. The data of this study analyzed using Paired Sample T-test and Wilcoxon Signed Ranks Test. The findings of this study show that new finansial intrument accounting standard PSAK 71) implementation impact to finansial performance (ROE) and liabilities (DAR and DER). This study also found that new lease accounting stardard impact to finansial performance (ROE and ROA) and liabilities (DAR). Moreover this study found that after implemnentation of PSAK 71 will be followed by ROE decreasing and DAR and DER increasing. Meanwhile, firm finansial performance that proxied by ROE and ROA decrease and DER increase since new lease accounting standard (PSAK 73) implemented by indonesian listed companies. This study conclude that new finacial instrument and lease accounting standard finansial performance and liabilities of indonesian listed companies. Indonesian listed companies deal with lower finansial performance and higher liabilities financing after apllying those new accounting standard.